2019
DOI: 10.1111/1750-3841.14681
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Multilayer Active Packaging Films with Controlled Release Property Based on Polypropylene/Poly(Vinyl Alcohol)/Polypropylene Incorporated with Tea Polyphenols

Abstract: The polypropylene/poly(vinyl alcohol)/polypropylene (PP/PVA/PP) multilayer active films with controlled release property were developed, of which the intermediate PVA layer was incorporated with 4% (w/w) tea polyphenols (TP) and the microporous PP films with different pore size were used as the internal controlled release layer. The SEM results showed that each layer of these films was agglutinated tightly. With increasing pore size from 171.05 to 684.03 µm, there were little effect on the films’ color and opa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Another example is proposed by [ 11 ] who produced active bilayer films using cassava starch and polyvinyl acetate (PVA) as biopolymers. In addition, other biopolymers are often used to develop this type of material, such as gelatin, potato starch, zein, and soy protein isolate [ 15 , 18 , 19 , 20 ].…”
Section: Recent Multilayer Packaging Developmentsmentioning
confidence: 99%
“…Another example is proposed by [ 11 ] who produced active bilayer films using cassava starch and polyvinyl acetate (PVA) as biopolymers. In addition, other biopolymers are often used to develop this type of material, such as gelatin, potato starch, zein, and soy protein isolate [ 15 , 18 , 19 , 20 ].…”
Section: Recent Multilayer Packaging Developmentsmentioning
confidence: 99%
“…The film samples (500 mg) were immersed into 100 mL of 10% Eth at 25°C. The amount of LMO in the 500 mg of film samples was determined similarly according to Chen et al (2019). The supernatants were extracted periodically, and examined at 417 nm using a UV-vis spectrophotometer.…”
Section: Lmo Release Propertymentioning
confidence: 99%
“…The antibacterial activity of starch-based film was positively correlated with the loading of nanoparticles, and the antibacterial activity against Gram-positive Staphylococcus aureus was stronger than Gram-negative Escherichia coli . Chen and Li [ 121 ] prepared composite films by in-situ reduction using carboxymethyl cellulose (CMC) and starch as reductants and stabilizers. The results showed that ACS film had apparent antibacterial activity against S. aureus and E. coli .…”
Section: Starch-based Active Filmsmentioning
confidence: 99%